2021
DOI: 10.1249/mss.0000000000002594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an “Active-Workstation” Cluster RCT on Daily Waking Physical Behaviors

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
(56 reference statements)
0
12
0
2
Order By: Relevance
“…Active workstations such as sit-to-stand desks, cycling desks, and treadmill desks can be used to improve health outcomes for employees who work in seated desk jobs by reducing sedentary behavior and increasing engagement in light physical activity. In a recent randomized-controlled trial examining the long-term effects of active workstations, employees using a treadmill desk engaged in fewer daily sedentary bouts at the workplace when compared to a sit-to-stand desk group and a control group at 12 months (Arguello et al, 2021 ). Furthermore, reviews of the active workstation literature have revealed that treadmill desks increase energy expenditure more than other types of active workstations (Tudor-Locke et al, 2014 ) and are associated with greater physiological benefits than a standing desk (MacEwen et al, 2015 ).…”
Section: Benefits Of Treadmill Desk Usementioning
confidence: 99%
“…Active workstations such as sit-to-stand desks, cycling desks, and treadmill desks can be used to improve health outcomes for employees who work in seated desk jobs by reducing sedentary behavior and increasing engagement in light physical activity. In a recent randomized-controlled trial examining the long-term effects of active workstations, employees using a treadmill desk engaged in fewer daily sedentary bouts at the workplace when compared to a sit-to-stand desk group and a control group at 12 months (Arguello et al, 2021 ). Furthermore, reviews of the active workstation literature have revealed that treadmill desks increase energy expenditure more than other types of active workstations (Tudor-Locke et al, 2014 ) and are associated with greater physiological benefits than a standing desk (MacEwen et al, 2015 ).…”
Section: Benefits Of Treadmill Desk Usementioning
confidence: 99%
“…This was a multicomponent intervention to decrease sedentary behavior in the workplace and comprised organizational, environmental, and individual-level strategies to target behavior change at both the individual and cluster levels [ 22 ]. The enrolled participants received initial face-to-face counseling sessions on the benefits of sitting less, standing, and moving more.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unclear whether active workstations reduce sitting in an all-or-none fashion, similar to that of exercise participation behavior, or whether they produce regular breaks from sitting throughout the day. Current knowledge on how active workstations alter physical behavior patterns consists of only a select number of metrics, such as usual or mean sedentary bout durations, selected duration stratifications of prolonged sedentary bouts (ie, >30 min), the number of sit-to-upright transitions or breaks from sedentary behavior, or the number of daily bouts of various physical behaviors [ 22 , 24 , 27 , 28 , 31 , 36 , 37 ]. Previously, we reported that our sit-to-stand and treadmill desk trial resulted in short-term improvements in standing (ie, 62-74 min/day) and stepping volume (ie, 41-49 min/day), with a pattern effect of treadmill desk users engaging in fewer daily sedentary bouts, whereas sit-to-stand desk users transitioned more frequently to upright physical behaviors [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five interventions were held in the United Kingdom (UK) [ 35 39 ] and 2 interventions in Canada [ 40 , 41 ]. The United States of America (USA) contributed with 5 sit-stand desk-based RCTs [ 12 , 42 45 ] and Japan with 1 intervention [ 46 ]. Notice that 14 out of the 23 RCTs were performed in countries belonging to the Commonwealth, and 19 out of 23 in English-speaking countries.…”
Section: Introductionmentioning
confidence: 99%